2015
DOI: 10.3762/bjoc.11.201
|View full text |Cite
|
Sign up to set email alerts
|

Cross metathesis of unsaturated epoxides for the synthesis of polyfunctional building blocks

Abstract: SummaryThe cross metathesis of 1,2-epoxy-5-hexene (1) with methyl acrylate and acrylonitrile was investigated as an entry to the synthesis of polyfunctional compounds. The resulting cross metathesis products were hydrogenated in a tandem fashion employing the residual ruthenium from the metathesis step as the hydrogenation catalyst. Interestingly, the epoxide ring remained unreactive toward this hydrogenation method. The saturated compound resulting from the cross metathesis of 1 with methyl acrylate was trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Various CM or RCM/hydrogenation sequences were next investigated and the hydrogenated products were obtained in good to excellent yield (Scheme ). Notably, the authors reported that a keto group is well tolerated, although high hydrogen pressure (up to 68 atm) was required for more challenging substrates …”
Section: Defining Tandem Catalysismentioning
confidence: 99%
“…Various CM or RCM/hydrogenation sequences were next investigated and the hydrogenated products were obtained in good to excellent yield (Scheme ). Notably, the authors reported that a keto group is well tolerated, although high hydrogen pressure (up to 68 atm) was required for more challenging substrates …”
Section: Defining Tandem Catalysismentioning
confidence: 99%
“…The insight gained from this work can be applied in the synthesis of similar compounds as well as in other uses of an epoxide as an olefin protecting group. For example, synthetic strategies including olefin metathesis have become common in organic chemistry, and recent examples conducted in the presence of a remote epoxide can be found based on cross metathesis with electron deficient olefins, 17 ring-closing olefin metathesis, 18,19 and ene-yne metathesis. 20 Given the ability to regenerate an olefin from an epoxide in the presence of additional olefins while preserving their stereochemistry, one can easily imagine application through sequences involving epoxidation, metathesis, and conversion of the epoxide back to an olefin.…”
mentioning
confidence: 99%